Hubungan Antara Kualitas Tidur dan Tingkat Kecemasan Pada Perawat yang Menjalani Shift Malam di Rumah Sakit - Oryzati Hilman; Naufal Muhammad Agna Fahreza (Jurnal Ners, 2026)
Nurses working in 24-hour healthcare facilities, such as hospitals, frequently experience disrupted sleep patterns due to irregular shift schedules. Sleep disturbances can negatively affect psychological conditions, including increased anxiety levels. This study aimed to determine the relationship between anxiety levels and sleep quality among nurses working night shifts in a hospital. This research employed a quantitative analytic observational method with a cross-sectional design. A total of 66 nurses from PKU Muhammadiyah Gamping Hospital, Sleman, Special Region of Yogyakarta, participated in this study. The findings revealed that most nurses had poor sleep quality (51.5%), while the majority did not experience anxiety (84.8%). Statistical analysis showed a significant relationship between sleep quality and anxiety levels (p = 0.001; p < 0.05), with a correlation coefficient of 0.63, indicating a strong association between the variables. In conclusion, there is a strong and significant relationship between sleep quality and anxiety levels among night-shift nurses. Effective sleep management is recommended to reduce the risk of anxiety and other psychological disorders among healthcare professionals.